Sexting: A Self Portrayal Trend Among Youths On Social Media? - UKWUEZE, Cornelius A; ABANEME, Ezinne Chioma (Socialscientia: Journal of Social Sciences and Humanities, 2021)
Sexting is defined as the sending, receiving, or forwarding sexually explicit messages, images, or photos through electronic means, particularly between cell phones. Media Researchers have raised alarm on the prevalence of sexting among adolescents and youths generally and the negative consequences associated with it. This paper, examines the prevalence and motivating factors for sexting among Nigerian youths to determine if it is a form of online self-portrayal. The study was anchored on two theories: The Uses and Gratification Theory and The Play Theory. The study area was universities in Imo state and three universities were sampled each from Federal, State and Private Universities which made up the study population. The survey design was adopted as the study methodology and the questionnaire was used as the data collection instrument. A sample size of 300 undergraduates was selected from three universities selected from federal, state and private Universities through multi-stage sampling technique. Findings from the study revealed that, the popularity of sexting among Nigerian youths was very high and it serves as a form of self-representation online but they are not aware of the negative consequences. Most of the youths engage in sexting because they believe that sexting help them to be known and attracts more attention to their profiles. Based on these findings, the study recommends among others that an intensive sensitization should be carried out, either through seminars, campaigns or publications to inform these youths of the negative consequences of Sexting and that parents and families as agents of socialization should intensify their sexual socialization roles.